Perfil dos cuidadores informais de idosos atendidos pelo Ambulatório de Gerontologia do HU-UFSCar e a necessidade de orientações - Martins, Gabriela (2022)
Introduction: The informal caregiver, who is represented by family members, friends or community members, is the most prevalent type of support for the elderly and therefore there is a need to strengthen their knowledge. Thus, evaluating them at the getiatric outpatient clinic is essential to identify the main needs for guidance regarding the care provided later at home. Objective: To characterize the profile of informal caregivers of the elderly assisted by the Gerontology Outpatient Clinic at HU-UFSCar, and the need for guidance in home care. Method: This is a quantitative, cross-sectional and correlational study, with fifty pairs of informal caregivers and the elderly they attend. Caregivers were evaluated via teleconsultation by applying the questionnaire to characterize the socioeconomic and health profile and the need for guidance, Zarit-Brief Burden Interview (ZBI-12), to assess the objective and subjective perception of burden and the Depression and Anxiety Scale. (HAD), to identify the presence of symptoms of depression and anxiety. In addition, information on the health status of the assisted elderly was collected by the caregiver's self-report. A Multidimensional Assessment Protocol for the Elderly was applied, with sociodemographic and health data, the Katz Scale and the Lawton and Brody Scale for the degree of dependence for basic and instrumental activities of daily living and the calculation of the Charlson Comorbidity Index (CCI) to consider secondary clinical conditions and link their repercussions on the prognosis of the elderly in the sample. For data analysis, multivariate Poisson Regression models were used to analyze the ZBI-12 and HAD scores as a function of a set of independent variables of interest. Results: Informal caregivers had a mean age of 54.7 years (±15.1), with a predominance of women (94%), married (40%), with a mean schooling of 9.4 years (± 4 ,7), most were children of care recipients (56%), lived in the same place as the elderly (80%), had an average age of 8.7 years (± 10.0) and 17.5 years hours of care per day (± 8.6) and who would like to receive more information/guidance about the care of the elderly (82%). Regarding health, caregivers had an average of 1.7 diseases (±1.2) and 1.82 medications of daily use (±1.6) and most of these caregivers showed the presence of care-related burden (60%), with unlikely symptoms of depression (78%) and anxiety (70%). The elderly had a mean age of 75.9 years (±9.3), most were female (72%), widowed (44%) and had a mean schooling of 4.26 years (±3.6 years). Regarding health, the mean number of diseases was 3.02 (±1.6) and the ICC was 4.2 (±1.5), with 32% of the elderly having a mortality risk of 85% in a year, 4.72 medications for daily use (±2.7) and half of the elderly sample (50%) was classified as independent for performing BADL and the majority (48%) as partially dependent for IADL. In addition, the correlations between caregivers' age in years and the elderly's ICC score established higher levels of caregiver burden. Unlike the care time spent on the elderly, which, when associated, showed less burden on the person who cares. Conclusion: These results reveal the need for interventions with the objective of controlling multimorbidity and delaying the development of complications that lead to dependence in the elderly, as well as practices that guarantee support for informal caregivers regarding the reduction of the burden related to the care of the elderly and of depressive and anxiety symptoms in this population, especially at the beginning of the formation of the elderly plus caregiver relationship.